El estrés psicosocial en la esteatosis hepática asociada a disfunción metabólica (MASLD): sobreposición desfavorable - Aleman F., Larissa; Dufeu G., María Soledad; Fuenzalida R., Catalina; Ortiz-López, Nicolás; Pinto L., Araceli; Simian M., Daniela; Cárdenas L., Gonzalo; Garrido I., Cristián; Cattaneo B., Máximo; Urzúa M, Álvaro; Guíñez F., Dannette; Roblero C., Juan Pablo; et al. (Revista Hospital Clínico Universidad de Chile, 2024)
The metabolic dysfunction-associated steatotic liver disease (MASLD)(1) is considered the leading cause of liver disease worldwide. It is a complex pathology, which includes a spectrum of diseases ranging from steatosis to advanced forms of liver damage, such as cirrhosis. Its prevalence has increased in recent years, becoming a relevant public health problem. It is characterized by fat accumulation in hepatocytes, which induces lipotoxicity, oxidative stress, inflammation, and consequently, liver damage. The mechanisms involved in MASLD progression are not fully understood. Also, the factors that determine the heterogeneous susceptibility towards liver fibrosis among patients, remain unresolved. In recent years, chronic stress has been described as a relevant risk factor in the progression of MASLD. The presence of stress is associated with alterations in the gut-liver-brain axis, which promotes systemic low-grade inflammation that reinforces the liver damage progression. This review aims to discuss the evidence about the role of psychosocial stress in MASLD and its association with the pathogenic mechanisms involved in liver damage.